2‐Aminoethylphosphonate utilization in Pseudomonas putida BIRD‐1 is controlled by multiple master regulators. (8th March 2022) - Murphy, Andrew R. J.; Scanlan, David J.; Chen, Yin; Bending, Gary D.; Hammond, John P.; Wellington, Elizabeth M. H.; Lidbury, Ian D. E. A.
Summary: Bacteria possess various regulatory mechanisms to detect and coordinate a response to elemental nutrient limitation. In pseudomonads, the two‐component system regulators CbrAB, NtrBC and PhoBR, are responsible for regulating cellular response to carbon (C), nitrogen (N) and phosphorus (P) respectively. Phosphonates are reduced organophosphorus compounds produced by a broad range of biota and typified by a direct C‐P bond. Numerous pseudomonads can use the environmentally abundant phosphonate species 2‐aminoethylphosphonate (2AEP) as a source of C, N, or P, but only PhoBR has been shown to play a role in 2AEP utilization. On the other hand, utilization of 2AEP as a C and N source is considered substrate inducible. Here, using the plant‐growth‐promoting rhizobacterium Pseudomonas putida BIRD‐1 we present evidence that 2AEP utilization is under dual regulation and only occurs upon depletion of C, N, or P, controlled by CbrAB, NtrBC, or PhoBR respectively. However, the presence of 2AEP was necessary for full gene expression, i.e. expression was substrate inducible. Mutation of a LysR‐type regulator, termed AepR, upstream of the 2AEP transaminase‐phosphonatase system (PhnWX), confirmed this dual regulatory mechanism. To our knowledge, this is the first study identifying coordination between global stress response and substrate‐specific regulators in phosphonate metabolism.